Gender-Based Violence and Political and Social Participation of Young Women Leaders in Colombia - López Andrade, Maria Catalina (2025)
This research aims to shed light on and understand the impact of gender-based violence on the exercise of leadership and political participation of young women in Colombia. To achieve this, the study examines the leadership trajectories of young women, focusing on their engagement in social mobilization and political and electoral processes. The methodology employed consisted of semi-structured interviews with women leaders from various regions of the country, aiming to identify the different forms of violence they experience in leadership roles and the barriers they face in political and social participation. The research process focused on the events that occurred within the framework of the National Strike in Colombia (April-June 2021), a series of mobilizations and protests that marked a social and political milestone for leaders from various sectors in the country. It highlights the significant roles women played during the national strike mobilizations, as well as the differentiated forms of violence they faced, including sexual, physical, and psychological violence. Additionally, it underscores the impact on their mental health and how traditional gender roles restrict their participation in decision-making spaces. The research also addresses structural and cultural barriers, including the security risks faced by women in leadership positions. Finally, it analyzes the influence of the national strike in creating opportunities for young women to politicize their struggles and transition their leadership into the electoral political sphere, despite the ongoing barriers and violence they face within social movements and political parties.